Influence of sustained elevated temperature on fly ash concrete - Vishwanath Prof. K.N.; Narayana Dr. S.; Bindiganavile Dr. V. (My University, 2025)
The paper represents the influence of fly ash on the behaviour of hardened concrete in compression under sustained elevated temperatures. With replacement levels up to 30% by mass of cement, 4 mixes were cast. Specimens were exposed to temperatures up to 300°C sustained for a period of 3 hour, after 28 days curing. The specimens were allowed to cool to room temperature and then tested under compression. Through X-ray diffraction the change in the composition was identified. This showed that, elevated temperatures till 300°C range favours formation of amorphous phases and the consumption of CH in the presence of fly ash. Based on the residual mechanical properties, it is concluded that blending with fly ash is a viable technique to sustain concrete at elevated temperatures.